Variation in Specialists’ Reported Hospitalization Practices of Children Sustaining Blunt Abdominal Trauma - Sokolove, Peter E (Western Journal of Emergency Medicine, 2013)
Introduction: Children with blunt abdominal trauma (BAT) are often hospitalized despite no intervention. We identified factors associated with emergency department (ED) disposition of children with BAT and differing computed tomography (CT) findings.Methods: We surveyed pediatric and general emergency physicians (EPs), pediatric and trauma surgeons regarding care of two hypothetical asymptomatic patients: a 9-year-old struck by a slow-moving car (Case 1) and an 11-month-old who fell 10 feet (Case 2). We presented various abdominal CT findings and asked physicians about disposition preferences. We evaluated predictors of patient discharge using multivariable regression analysis, adjusting for hospital and ED characteristics, and clinician experience. Pediatric EPs served as the reference group.Results: Of 2,003 eligible surveyed, 636 (32%) responded. For normal CTs, 99% would discharge in Case 1 and 88% in Case 2. Prominent specialty differences included: for trace intraperitoneal fluid (TIF), 68% would discharge in Case 1 and 57% in Case 2. Patients with TIF were less likely to be discharged by pediatric surgeons (Case 1: OR 0.52, 95% CI 0.32, 0.82; Case 2: OR 0.49, 95% CI 0.30, 0.79). Patients with renal contusions were less likely to be discharged by pediatric surgeons (Case 1: OR 0.55, 95% CI 0.32, 0.95) and more likely by general EPs (Case 1: OR 1.83, 95% CI 1.25, 2.69; Case 2: OR 2.37, 95% CI 1.14, 4.89).Conclusion: Substantial variation exists between specialties in reported hospitalization practices of asymptomatic children after abdominal trauma with minor CT findings. Better evidence is needed to guide disposition decisions. [West J Emerg Med. 2013;14(1):37-46.]